Search for B+ meson decay to a+1(1260)K*0(892) - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present a search for the decay B+→a+1(1260)K*0(892). The data, collected with the BABAR detector at the SLAC National Accelerator Laboratory, represent 465×106B¯¯¯B pairs produced in e+e− annihilation at the energy of the Υ(4S). We find no significant signal and set an upper limit at 90% confidence level on the product of branching fractions B(B+→a+1(1260)K*0(892))×B(a+1(1260)→π+π−π+) of 1.8×10−6.
The Babar Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, U. Uwer [und viele weitere]
Gesehen am18.08.2023
Im Titel ist das Pluszeichen hochgestellt, die Zahl "1" tiefgestellt, "0" ist nach "K" hochgestellt
Im Titel ist [ast] als Tropfensternchen dargestellt und hochgestellt